KREATIFITAS PEMBUATAN IKLAN PRODUK ROKOK DI INDONESIA - Bedjo Tanudjaja, Bing (Institute of Research and Community Outreach - Petra Christian University, 2002)
Cigarettes products advertisement are always limited by the rules%2C whether it is from the government either from the international one. It seems that the creativity is always needed to make the cigarettes advertisement without limited by that kind of rules. Abstract in Bahasa Indonesia : Iklan produk rokok selalu dibatasi oleh peraturan-peraturan%2C baik peraturan pemerintah maupun peraturan internasional. Untuk itu dibutuhkan kreativitas agar bisa membuat iklan rokok tanpa harus terbentur peraturan-peraturan tersebut. cigarettes product advertisement%2C rules%2C creativity.